Fiqh al-Biah ‎(Formulasi Konsep al-Maqasid al-Shari’ah ‎dalam Konservasi dan Restorasi Lingkungan)‎ - M. Hasan Ubaidillah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
Human beings are bestowed the right to manage and make use of nature to fulfil their needs. In making use and exploiting mother nature, human beings are not allowed to cause natural disaster. Therefore, disaster mitigation and prevention is a necessity and has to be implemented from religious perspective as well. In Islam, such effort can be executed through the concept of islamic environtmental law (fiqh al-biah) which is built upon the framework of al-maqasid al-shari’ah. In this context, the theory of maslahah mursalah is the basic argument stateing that islamic law is intended to uphold the needs of the masses and functions to give benefit and prevent harms. Further, the formulation of conservation concept and environmental restoration in fiqh biah must be based on (1) the nature as the ‘signs’ of God, (2) Shariah emphasis on the need of environtmental balance by encouraging good treatment of all creatures and environment, (3)the idea of continuous environtmental restoraion, (4)the obligatory responsibility of human being as the vice gerent of God on earth, and (5)the sthengthening the conviction as the pillar of humanity as a key point to the success of creating the balance between social and environmental piety.